A novel fungal-targeted drug delivery system dectin-1-targeted-PEG-amino acid polymer block enhances antifungal activity and reduces cytotoxicity of amphotericin B - Inukai, Tatsuya; Chen, Pengwen; Kokuba, Hiroko; Cabral, Horacio; Nakamura, Shigeki (Journal of drug delivery science and technology, 2024)
We investigated whether the cytotoxicity of the antifungal drug amphotericin B (AmB) could be mitigated using Dectin-1 (DEC)-installed-polymeric micelles based on poly(ethylene glycol) (PEG)-amino acid block copolymers. In this study, DEC-installed micelles formed by carboxydimethylmaleic anhydride-modified PEG-poly(L-lysine) (PEG-pLL(CDM)) or PEG-poly(β-benzyl-L-aspartate) (PEG-pBLA) were prepared and compared with uninstalled DEC-micelles. The polymeric micelles confirmed the acquisition of accumulation on fungi by installing DEC. DEC-micelles loaded with AmB (DEC-AmB/m) showed higher antifungal activity in vitro than AmB/m. The administration of DEC-AmB/m with 20 μg/mL of AmB to cultured cells inhibited the release of intracellular lactate dehydrogenase. In the evaluation of treatment efficacy using an Aspergillus-infected silkworm model, DEC-AmB/m at 5 μg/larva (amphotericin B equivalent) improved silkworm survival compared with AmB 5 μg/larva treatment. These results suggest that drug-loaded micelles may improve the clinical efficacy and safety of AmB and highlight the potential of DEC-PEG-poly(amino acids) modification for compound delivery against fungal infections. [Display omitted]